2022
DOI: 10.3389/fpls.2022.863076
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Plastid Developmental Genes Coincides With a Reversion to Monoplastidy in Hornworts

Abstract: The first plastid evolved from an endosymbiotic cyanobacterium in the common ancestor of the Archaeplastida. The transformative steps from cyanobacterium to organelle included the transfer of control over developmental processes, a necessity for the host to orchestrate, for example, the fission of the organelle. The plastids of almost all embryophytes divide independently from nuclear division, leading to cells housing multiple plastids. Hornworts, however, are monoplastidic (or near-monoplastidic), and their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…HY5's absence in these two species could be the result of a genome/transcriptome annotation error (Cheon et al, 2020). However, hornwort emergence and diversification were accompanied by major instances of gene loss (MacLeod et al, 2022), so HY5's absence in A. punctatus and L. dussii could be explained by this phenomenon.…”
Section: Functional Conservation Of Uvr8 Signalling In Chlorophytes A...mentioning
confidence: 97%
See 1 more Smart Citation
“…HY5's absence in these two species could be the result of a genome/transcriptome annotation error (Cheon et al, 2020). However, hornwort emergence and diversification were accompanied by major instances of gene loss (MacLeod et al, 2022), so HY5's absence in A. punctatus and L. dussii could be explained by this phenomenon.…”
Section: Functional Conservation Of Uvr8 Signalling In Chlorophytes A...mentioning
confidence: 97%
“…However, whether UVR8 signalling is conserved in hornworts is unknown as the lack of experimental data prevent this question from being answered. However, data from phylogenomic analyses (MacLeod et al, 2022) indicate that orthologues for core UVR8 components are found in most hornworts; with the exception of Anthoceros punctatus (Bonn ecotype) and Leiosporoceros dussii, which appear to have differentially lost HY5. HY5's absence in these two species could be the result of a genome/transcriptome annotation error (Cheon et al, 2020).…”
Section: Functional Conservation Of Uvr8 Signalling In Chlorophytes A...mentioning
confidence: 99%
“…Interestingly, some of the unique hornwort characters vary even between different families. For example, the number of chloroplasts per cell or the presence of pyrenoids, stomata and arbuscular mycorrhizal symbiosis ( Villarreal and Renner, 2012 ; Desiro et al., 2013 ; Frangedakis et al., 2021a ; MacLeod et al., 2022 ) ( Figure 3B ). Thus, comparative studies within hornworts can help identify the genetic mechanisms that control these characters.…”
Section: The Unique Biology Of Hornwortsmentioning
confidence: 99%
“…This smaller gene repertoire, together with lineage-specific gene losses, provides a useful avenue to investigate their role in polyplastidy evolution. There have also been losses of plastid-related genes specifically within hornworts ( MacLeod et al., 2022 ). Most notable in this regard are the distributions of Accumulation and Replication of Chloroplasts 3 ( ARC3 ) and the Filamentous Temperature Sensitive Z (FtsZ) gene family ( FtsZ 1, 2 and 3 ) in hornworts.…”
Section: The Unique Biology Of Hornwortsmentioning
confidence: 99%
See 1 more Smart Citation